Penanganan Keadaan Khusus pada Operasi Kereta Api - Nugroho, Agus; Suryono, Totok; Wibisono, Indarto; Saribanon, Euis (Dinasti Review, 2024)
In organizing train operations in Indonesia, especially in Java, apart from planning, controlling and evaluating train operations under normal/ordinary conditions, based on existing data and experience, several planning and control scenarios are needed for special conditions/services, handling critical situations, also handling emergencies. In terms of regulations (determination & announcement) of train operations, in the form of GAPEKA for normal circumstances, MALKA, PPK and WAM scenarios are also prepared as alternative regulations outside GAPEKA (PT Kereta Api Indonesia Service Regulation No. 19 of 2011). In everyday life, apart from these scenarios, anticipation is also needed to provide guidelines for handling them, so that they support the train travel operation scenarios. In order to provide references, guidelines, flow and supporting resources on how to deal with several of these situations, both predictable, incidental and unexpected, then the plan for handling special situations must be formulated properly and completely and in accordance with various possible circumstances. The formulation of handling special situations is important. Handling these special situations is still different for special, critical or emergency situations/services